2012
DOI: 10.1152/ajprenal.00547.2011
|View full text |Cite
|
Sign up to set email alerts
|

Chronic use of chloroquine disrupts the urine concentration mechanism by lowering cAMP levels in the inner medulla

Abstract: Chloroquine, a widely used anti-malaria drug, has gained popularity for the treatment of rheumatoid arthritis, systemic lupus erythematosus (SLE), and human immunodeficiency virus (HIV). Unfortunately, chloroquine may also negatively impact renal function for patients whose fluid and electrolyte homeostasis is already compromised by diseases. Chronic administration of chloroquine also results in polyuria, which may be explained by suppression of the antidiuretic response of vasopressin. Several of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…It has been demonstrated in in vitro and in vivo studies on the rat inner medullary collecting ducts that chloroquine inhibits both basal and arginine vasopressin (AVP)-induced cAMP production. 30, 31 Our data show a greater reduction in cholangiocyte cAMP levels when the drugs are used together than when they are used alone. Thus, it appears that both drugs via different mechanisms affect cAMP signaling.…”
Section: Discussionmentioning
confidence: 61%
“…It has been demonstrated in in vitro and in vivo studies on the rat inner medullary collecting ducts that chloroquine inhibits both basal and arginine vasopressin (AVP)-induced cAMP production. 30, 31 Our data show a greater reduction in cholangiocyte cAMP levels when the drugs are used together than when they are used alone. Thus, it appears that both drugs via different mechanisms affect cAMP signaling.…”
Section: Discussionmentioning
confidence: 61%
“…Consequently, protein abundance of AQP2 is increased as a regulatory mechanism to long periods of water deprivation and/or high circulating levels of vasopressin [37] . Several animal models of acquired NDI including hypokalemia, hypercalcemia, ureteral obstruction, chloroquine and lithium nephrotoxicity have decreased AQP2 expression in the inner medulla [23] , [38] [40] ; hence the need to understand the transcriptional regulation of the AQP2 gene. It is generally accepted that the cAMP-mediated regulation of AQP2 gene transcription is mediated by CREB binding to a documented functional CRE element [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Taking 4-AQ is associated with the onset of chronic renal failure [78,143]. 4-AQ-induced polyuria is also described [144].…”
Section: Induced Lesionsmentioning
confidence: 99%
“…4-AQ-induced polyuria is multifactorial. On the one hand, 4-AQ downregulates the water channel aquaporin-2 and the Na + -K + -2Cl − -cotransporter (NKCC), causing urinary sodium loss and an increase in diuresis [144] . On the other hand, it is showed that CQ modulates the synthesis of plasma arginine vasopressin [151 , 152] and its effect on the kidney [153] , disrupting the urine concentration mechanisms.…”
Section: Introductionmentioning
confidence: 99%